Kinetics and equilibrium studies of the adsorption of nickel (II) ions from aqueous solution onto modified natural and synthetic iron oxide - Adolphe, Kouoh Sone Paul-Michel; Merlain, Tagne Guy; Blaise, Lekene Ngouateu René; Desire, Belibi Belibi Placide; Julius, NdiNsami; Daouda, Kouotou; Julius, Ghogomu Numbonui; Solomon, Anagho Gabche; Joseph, Ketcha Mbadcam (International Journal of Basic and Applied Sciences, 2015)
The present paper reports on the kinetic and equilibrium studies of the adsorption of Nickel(II) ions from aqueous solution onto modified natural iron oxide (NAT) from Mbalam (East Region of Cameroon) and synthetic iron oxide (SYNTH). The parameters investigated using batch techniques include, the contact time, adsorbent mass, pH and initial metal ion concentration. The experimental results obtained showed that, the optimum pH of 6 for bothadsorbents with an equilibrium time of 30 minutes was sufficient. The kinetic data correlated well with the pseudo-first-order and pseudo-second-order kinetic models for both the adsorbents based on the correlation coefficients (R2) obtained. The adsorption processes followed both the Langmuir and the Tempkin adsorption models for the natural iron oxide, whereas the Freundlich and Tempkin adsorption models fitted well the adsorption data for the synthetic iron oxide. The maximum quantity of Nickel(II) ions adsorbed was 250 mg/g for the two adsorbents. These results revealed a high adsorption capacity of natural iron oxide which is comparable to that of synthetic iron oxide.